UPAYA PENINGKATAN KESEHATAN IBU HAMIL MELALUI EDUKASI MENGGUNAKAN LEMBAR BALIK KEPADA KADER DAN IBU HAMIL - Rubiati Hipni; Tri Tunggal; Novi Ismarini (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The World Health Organization (WHO) estimates that 830 women in the world and in Indonesia 38 mothers die every day due to complications from pregnancy and the birth process (WHO, 2019). K1 and K4 visits in the working area of the Karang Intan 2 Community Health Center, Banjar Regency from January to May 2022 were not optimal, it was found that the K1 visit coverage of 38.79% and K4 34.35% was still less than the expected K1 and K4 achievement percentage. The programs at posyandu are also not much developed due to the limitations and lack of knowledge of cadres. Efforts to carry out training of cadres in efforts to improve the health of pregnant women through education using feedback sheets for cadres and pregnant women in the working area of Karang Intan 2 Health Center, Banjar Regency. This service aims to increase the knowledge and understanding of cadres and pregnant women regarding how to improve the health status of pregnant women in the Karang Intan 2 Health Center Working Area, Banjar Regency. The method involves training and mentoring for cadres using Power Point media, videos, flip sheets and leaflets. Participants consist of 20 cadres from PKM Partners, 10 pregnant women, 1 midwife and 1 nutritionist at Karang Intan 2 Community Health Center, Banjar Regency, evaluated through pre-test and post-test as well as monitoring and evaluation by assessing cadre counseling for pregnant women at the posyandu. The results show that there is an increase in improvement from before, this shows that the material presented can be understood by cadres and pregnant women well